Essentials of personnel assessment and selection - Guion, Robert M. (Lawrence Erlbaum Associates, 2006)
(from the book) Essentials of Personnel Assessment and Selection distills and updates the "essentials" from Guion's best-selling 1997 book Assessment, Measurement, and Prediction for Personnel Decisions. This new textbook gives managers and students the nuts and bolts of assessment processes and selection techniques. It covers basic and advanced concepts in a straight-forward, readable style. The book is certainly appropriate for use as a text for advanced undergraduates and master's level students interested in becoming users of research-based assessment and selection information and techniques.